Metabolomics combined with transcriptomics reveals the formation mechanism of different leaf colors of Heuchera micrantha - Wang, Yuxi; Tang, Yumeng; Chen, Xi; Yang, Xiaodong; Zhou, Qi; Hu, Yueheng; Meng, Xiaohua; Peng, Jialin (Frontiers in Plant Science, 2025)
IntroductionThe vivid colors of color-leafed plants endow plants with unique ornamental value. At present, there are many researches focusing on the mechanism of flower color formation, while there is less interesting research on color-leafed plants. As an excellent color-leafed plant, Heuchera micrantha has only been studied for its pigment content and physiological characteristics, and the mechanism of color-leafed formation has not been characterized yet.MethodsIn this study, we used two varieties of Heuchera micrantha with green and red leaves as materials, and employed a combination of metabolomics and transcriptomics to reveal the molecular mechanisms underlying the formation of different color leaves.ResultsThrough observation of phenotype, analysis of metabolomics and transcriptomics, and combined analysis of multi-omics, it was found that differential metabolites and differentially expressed genes were enriched in flavonoid metabolism and related pathways. Nine MYB and bHLH transcription-factor candidates implicated in flavonoid metabolism were selected and functionally annotated; five are predicted to act as activators and four as repressors of the flavonoid biosynthetic pathway.DiscussionIn summary, this study provides important insights into the coloring mechanism of color-leafed plants and provides gene reserves for subsequent targeted breeding.